Eight Reasons We Are Given Not to Worry About the U.S. Deficits - Frankel, Jeffrey (World Bank, Washington, DC, 2017)
The large U.S. current account deficit over the last decade-and the corresponding surpluses in China and elsewhere-has been interpreted in two very different ways. Many mainstream economists view the phenomena as primarily the outcome of a low rate of national saving in the United States, beginning with a large budget deficit (the other half of the 'twin deficits'). In this first view, the current account deficit is unsustainable, and will eventually result in a sharp depreciation of the dollar. But this unsustainability view has been challenged by a variety of other economists, with equally impeccable credentials. This paper enumerates eight arguments that they have given as to why we need not worry about the current account deficit. The paper is skeptical of all eight, and sides with the unsustainability view. But they deserve a hearing. The eight are: 1) the siblings are not twins; 2) alleged investment boom; 3) low U.S. private savings; 4) global savings glut; 5) its a big world; 6) valuation effects pay for it; 7) intermediation rents pay for it; and 8) second Bretton woods.